Differentiating children with familial Mediterranean fever from other recurrent fever syndromes: The utility of new Eurofever/PRINTO classification criteria - Rabia Miray Kışla Ekinci,; Sibel Balcı,; Ahmet Hakan Erol,; Dilek Karagöz,; Derya Ufuk Altıntaş,; Atıl Bisgin, (Archives of Rheumatology, 2021)
Objectives: In this study, we aimed to investigate the performance of Eurofever Registry and the Paediatric Rheumatology International Trials Organisation (PRINTO) classification criteria in pediatric patients with familial Mediterranean fever (FMF). Patients and methods:This retrospective, cross-sectional study included a total of 130 pediatric FMF patients (67 males, 63 females; mean age: 12.4±3.6 years; range, 2.5 to 17.7 years) with at least one M694V mutation in MEFV gene between July 2010 and July 2019. Demographic features and disease characteristics were recorded. The control group was consisted of 41 patients (19 males, 22 females; mean age: 7.8±4.0 years; range, 2.1 to 17.8 years) with other hereditary autoinflammatory diseases (AIDs), including periodic fevers with aphthous stomatitis, pharyngitis, and adenitis syndrome (n=30), mevalonate kinase deficiency (n=9), and tumor necrosis factor receptor-associated periodic syndrome (n=2). Sensitivity and specificity of the Eurofever/PRINTO classification criteria were calculated. Results: The sensitivity and specificity were 97.7% and 56.1% for Yalcinkaya-Ozen criteria, respectively and 93.1% and 90.2% for Tel Hashomer criteria, respectively. The Eurofever/PRINTO classification criteria reached a sensitivity and specificity of 94.6% and 82.9% and 93.1% and 80.5%, respectively, when genetic plus clinical criteria and clinical-only criteria were applied. Conclusion: The Eurofever/PRINTO classification criteria have a comparable sensitivity for avoidance of FMF underdiagnosis in childhood. The Yalcinkaya-Ozen criteria have the highest sensitivity without a significant specificity. The Tel Hashomer criteria and Eurofever/PRINTO classification criteria were superior to Yalcinkaya-Ozen criteria to differentiate FMF from other AIDs, thus leading to less complications relevant to underdiagnosis of other AIDs.